Implementation Of the Prosperous Family Card Program in Improving Community Welfare Based Van Meter and Van Horn Analysis : Study in Bunulrejo Village, Malang City - Sari, Yuli Indah; Hardianto, Willy Tri; Purwatiningsih, Annisa; Lestari, Asih Widi (Sawala : Jurnal Administrasi Negara, 2023)
The Prosperous Family Card (KKS) is one of the compensation package programs proposed by the government to help poor families so that those who live in poverty can be covered with this card which can reduce the problem of poverty and improve community welfare. The purpose of this research is to find out the implementation of the Prosperous Family Card program to improve community welfare and to find out the supporting and inhibiting factors for implementing the Prosperous Family Card program in community empowerment efforts. This research uses qualitative methods by collecting data through observation, interviews, and documentation. Determining informants was carried out using snowball sampling. Data analysis was carried out through the stages of data collection, data presentation, and conclusion. From this research, the results showed that the program's implementation involved continuous and intense socialization and regular monitoring regarding the distribution of aid, but it is very unfortunate that the program still had less valid outreach and data for less fortunate communities.